Editorial Perspective: How should child psychologists and psychiatrists interpret FDA device approval? Caveat emptor - Arns, Martijn; Loo, Sandra K.; Sterman, M. Barry; Heinrich, Hartmut; Kuntsi, Jonna; Asherson, Philip; Banaschewski, Tobias; Brandeis, Daniel (The journal of child psychology and psychiatry, 2016)
Recently several new tests have received US Federal Drug Administration (FDA) marketing approval as aids in the diagnostic process for attention deficit hyperactivity disorder (ADHD), including the Neuropsychiatric electroencephalogram (EEG)-Based ADHD Assessment Aid (NEBA) Health test. The NEBA test relies upon an EEG-based measure, called the theta to beta ratio (TBR). Although this measure has yielded large differences between ADHD and non-ADHD groups in studies prior to 2009, recent studies and a meta-analysis could not replicate these findings. In this article, we have used the NEBA device as an exemplar for a discussion that distinguishes between FDA de novo marketing approval for a device and any claims that that device is empirically supported, scientifically validated with replicated findings. It is understood that the aims of each differ; however, for many, including the lay public as well as some mental health professionals, these terms may be confused and treated as though they are synonymous. With regard to the TBR measure, there is no reliable association or replication for its clinical usage in the ADHD diagnostic process. The recommendation for potential consumers of the NEBA Health test (as well as perhaps for other existing FDA-approved diagnostic tests) is caveat emptor (let the buyer beware!).
EVALuna2:23889